FINANCIAL RESULT ANALYSIS OF AGROTOURISTIC FARMS ACTIVITIES IN SIEDLCE REGION - Sosnowski, Jacek; Ciepiela, Grażyna (Acta Scientiarum Polonorum. Oeconomia, 2011)
In order to estimate the financial result of tourism activities in 2006 and 2007, 87 farms providing touristic services in the region of Siedlce were examined. Questionnaire, consisting of 27 questions regarding the size of the accommodation and the economic aspects of touristic activities, was sent to the farms owners. The obtained data were analyzed graphically and in form of tables as well as used them to calculate the following economic indicators: the economic size and the rate of rural recreational space, the index of the average number of nights and indicators analyzing the income compared to the demand (POR) and the supply (Yield). The value of direct costs, revenue and gross margin were also calculated. Statistical analysis was conducted by calculating the Pearson correlation coefficient (r) and coefficient of determination (R2). The study showed that in touristic farms in the Siedlce region in 256 rooms, mostly 2- and 3-beds, there are 673 beds. The average annual gross margin of touristic activities amounts to the value in the range of 2,383.1 to 12,878.96 PLN z and this value proved to be significantly correlated with the attractiveness rate of the particular rural recreational space.